PEMAHAMAN MULTIKULTURAL MELALUI BIMBINGAN KELOMPOK BAGI FORUM ANAK DESA - Firdaus, Azzahro; Khusumadewi, Ari; Purwoko, Budi; Winingsih, Evi (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2024)
Abstract: Multicultural, as cultural diversity, One of the important issues needed for the Village Children's Forum is multicultural understanding. This research aims to determine the success of using Group Guidance services in providing an understanding of multiculturalism for the Village Children's Forum. This research uses the Systematic Literature Review (SLR) method using PRISMA (Preferred Reporting Items For Systematic Reviews And Meta Analyses) guidelines. A total of 7 journals in the period 2019 - 2024 used Google Scholar with the keywords